A Novel Pathogen Detection System Combining a Nucleic Acid Extraction Biochip with a Perovskite Photodetector - Zhuo Gao; Pan Wang; Chang Chen; Jian Duan; Shilun Feng; Bo Liu (Micromachines)
The increasing spread of infectious diseases caused by pathogenic microorganisms underscores the urgent need for highly sensitive, portable, and rapid nucleic acid detection technologies to facilitate early diagnosis and effective prevention. In this study, we developed a fluorescence-based nucleic acid detection platform that integrates a microfluidic chip with an all-inorganic perovskite photodetector. The system enables integrated operation of nucleic acid extraction, purification, and amplification on a microfluidic chip, combined with real-time electrical signal readout via a CsPbBr3 perovskite photodetector. Experimental results indicate that the photodetector exhibits high responsivity at 530 nm, aligning well with the primary emission peak of FAM. The system demonstrates a strong linear correlation between photocurrent and FAM concentration over the range of 0.01–0.4 μM (R2 = 0.928), with a low detection limit of 0.01 μM and excellent reproducibility across multiple measurements. Validation using FAM standard solutions and Escherichia coli samples confirmed the system’s reliable linearity and signal stability. This platform demonstrates strong potential for rapid pathogen screening and point-of-care diagnostic applications.